(3ebUhQI aj GdUfYI GdEdgjIs - (3NGdO Hf jRjO Hf eYGhjg Hf CHj SajGf, CHh gGTe,J (B90 (3g` s
(3ChdgG (B:s
(3Ydjc HTF ai GdSeGhGJ SGcf hjQei Hg GdTjWGf Ef QGe Cf jQbi s
(3BNQgG (B:s
(3SJYde Ef WGdJ MjGJi HbQHce MjGI HeG CYjJ Hg GdedI GdChdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B216 - (3U(B217s
(3JHUQI GdYfhGf (B:s
(3fXe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B98s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B204 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs